High‐Performance Lithium–Air Battery with a Coaxial‐Fiber Architecture. (1st March 2016) - Zhang, Ye; Wang, Lie; Guo, Ziyang; Xu, Yifan; Wang, Yonggang; Peng, Huisheng
Abstract: The lithium–air battery has been proposed as the next‐generation energy‐storage device with a much higher energy density compared with the conventional lithium‐ion battery. However, lithium–air batteries currently suffer enormous problems including parasitic reactions, low recyclability in air, degradation, and leakage of liquid electrolyte. Besides, they are designed into a rigid bulk structure that cannot meet the flexible requirement in the modern electronics. Herein, for the first time, a new family of fiber‐shaped lithium–air batteries with high electrochemical performances and flexibility has been developed. The battery exhibited a discharge capacity of 12 470 mAh g −1 and could stably work for 100 cycles in air; its electrochemical performances were well maintained under bending and after bending. It was also wearable and formed flexible power textiles for various electronic devices.